2020
DOI: 10.31025/2611-4135/2020.14031
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical modelling for recycling-oriented classification of shredded spent flat monitor products based on HyperSpectral Imaging

Abstract: The number of flat monitors from televisions, notebooks and tablets has increased dramatically in recent years, thus resulting in a corresponding rise in Waste from Electrical and Electronic Equipment (WEEE). This fact is linked to the production of new high-performance electronic devices. Taking into account a future volume growth trend of WEEE, the implementation of adequate recycling architectures embedding recognition/classification logics to handle the collected WEEE physical-chemical attributes, is thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…HSI is a cutting-edge approach to waste management that is rapidly gaining popularity as a quality control tool and as a core for sorting engines in several recycling processes [9]. Different HSI-based approaches have been proposed for plastic recycling [10][11][12], Construction and Demolition Waste (C&DW) recycling [13,14] and WEEE recycling [15,16].…”
Section: Polymer Typical Applicationsmentioning
confidence: 99%
“…HSI is a cutting-edge approach to waste management that is rapidly gaining popularity as a quality control tool and as a core for sorting engines in several recycling processes [9]. Different HSI-based approaches have been proposed for plastic recycling [10][11][12], Construction and Demolition Waste (C&DW) recycling [13,14] and WEEE recycling [15,16].…”
Section: Polymer Typical Applicationsmentioning
confidence: 99%
“…NIR reflectance spectra indicate material composition due to the existence of certain chemical bonds (e.g., O-H, N-H, C-H, S-H,...) [7,8]. Several HSIbased strategies have been developed in recent years for the effective recycling of plastic [9,10], the handling of waste from electrical and electronic equipment [11,12], and the management of waste from construction and demolition [13,14]. The literature has shown that the utilization of HSI in the waste sector significantly impacts the efficacy of several stages of the circularity process, such as material selection, component identification, quality control at each stage of treatment, and so on.…”
Section: Introductionmentioning
confidence: 99%